2015
DOI: 10.1039/c5ta05279c
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry of La0.6Sr0.4CoO3−δ thin films and its impact on the oxygen surface exchange resistance

Abstract: Correlation between the surface chemistry of LSC thin films analyzed by LEIS and ICP-MS and the oxygen exchange kinetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
130
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(157 citation statements)
references
References 50 publications
26
130
1
Order By: Relevance
“…This suggests that the as-prepared LSCF particles are terminated by a single SrO rocksalt layer. A similar result was obtained by the same method on as-prepared LSC thin films 16,24 and by low energy ion scattering measurements on as-prepared LSCF thin films, 25 despite different thermal history. The aged LSCF electrode surfaces showed a strongly enhanced amount of Sr (from 1.30 ± 0.27 to 3.90 ± 0.92 nmol/cm 2 ), see Fig.…”
Section: Resultssupporting
confidence: 83%
“…This suggests that the as-prepared LSCF particles are terminated by a single SrO rocksalt layer. A similar result was obtained by the same method on as-prepared LSC thin films 16,24 and by low energy ion scattering measurements on as-prepared LSCF thin films, 25 despite different thermal history. The aged LSCF electrode surfaces showed a strongly enhanced amount of Sr (from 1.30 ± 0.27 to 3.90 ± 0.92 nmol/cm 2 ), see Fig.…”
Section: Resultssupporting
confidence: 83%
“…6,10,17,19,22,34 The degradation on LSC at elevated temperatures renders itself in two apparent ways. These are the formation of Sr-rich precipitates at the surface, as in the present study, and the formation of a thin SrO termination layer at the top surface shown by low energy ion scattering and by ICP mass spectroscopy.…”
Section: Discussion On Implicationsmentioning
confidence: 99%
“…The preferred cathode materials for SOFC are mainly mixed ionic and electronic conducting (MIEC) perovskites like (La,Sr)(Co,Fe)O 3−δ (LSCF) and (La,Sr)CoO 3−δ (LSC). These materials deliver a high electrochemical performance, but due to the segregation of the Sr from the A-site of the perovskite lattice to the surface (Finsterbusch et al, 2012;Rupp et al, 2015), they are prone to reacting with volatile Cr species (Simner et al, 2006). According to the nucleation theory (Jiang and Zhen, 2008), the degradation mechanism is believed to be driven by a kinetically fast chemical reaction between the segregated Sr species and the volatile Cr species.…”
Section: Introductionmentioning
confidence: 99%